KEIMANAN ABU THALIB (Studi Komparatif Terhadap Tafsir Ibn Kasir dan Tafsir al-Mizan) - Yusri, Diyan (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2017)
Abu Talib's faith in the realm of Islamic thought still has a very long debate. Some scholars have claimed that he is an infidel, while others have claimed that he was a believer. Abu Talib was not uncommon also mixed up in political issues at the time of the power held by Mu'awiya sought to discredit Ali and his family. In the Koran, there are many verses that are considered by some scholars that the verses 113-114, al-Qasas verse 56, Surah al-An'am verse 26, and other letters relating to the faith of Abu Talib. The study was written as a reflection of the author's interest in knowing more about the subject by focusing Ibn Kathir's interpretation of the study as a Sunni interpretation and interpretation Tabataba'i as a homage to Shiite interpretation. The equation of these two interpreters is that Ibn Kathir explicitly says that these verses descend are addressed to Abu Talib (The Prophet's Uncle), who tells of Abu Talib's refusal to recite the two sentences of the shahadah at the end of his life, and still holds to his former religion Religion Abdul Mutallib. So also with T{abat{aba?i who said that Abu Talib died in a state of no faith and still hold on to the religion of his ancestors. While the location of the differences between them is contained in the interpretation of the letter al-An'am Ibn Kathir says the verse goes down with regard to Abu Talib who defends the Prophet to carry out his da'wah. T{abat{aba?i is different from Ibn Kathir in the explanation of his riwayah, namely the interpretation of 'Iyasi and Qumi's commentary, he says from the line of Ahl Bait that Abu Talib is a believer based on his evidence and his sayings. Essentially these two interpretations are the same, the most notable distinction lies only in the flow they profess, Ibn Kathir as a Sunni interpreter, T{abat{aba?i as a Shiite interpreter.